Glutathione, a key compound for As accumulation and tolerance in soybean plants treated with AsV and AsIII - Vezza, Mariana Elisa; Luna, Dario Fernando; Agostini, Elizabeth; Talano, Melina Andrea (Elsevier, 2019)
Despite soybean (Glycine max L.) is often cultivated in areas contaminated with arsenic (As) which causes deleterious effects on its growth, little is known about tolerance mechanisms in response to As exposure. In particular, glutathione (GSH) (γ-glutamyl-cysteinyl-glycine) has antioxidant properties and is precursor of phytochelatin (PCs) synthesis, thus its role in As-treated plants would be relevant. We proposed to assess the GSH role in the response to arsenate (AsV) and arsenite (AsIII) in soybean plants using BSO (L-buthionine-sulfoximine), an inhibitor of its synthesis. BSO treatment was efficient to reduce GSH production in roots and leaves. However, GSH reduction was lower in As/BSO-treated plants compared to control/BSO-treated plants, which suggests an As-induced activation of its synthesis. As a consequence, a decrease in PCs content and PC:As ratio in roots was observed. In addition, a reduction of antioxidant activity, including ascorbate and glutathione peroxidase activity, was detected under BSO treatment, which resulted in an increase of membrane damage and root cell death. Also, low GSH content increased inhibitory effects of As on gas exchange and PSII yield, which could explain the reduction in aerial parts biomass, mainly under AsIII-treatment. BSO-exposure also caused a significant decrease of As accumulation in roots, although increased its translocation to leaves. Our findings suggest that GSH regulated As stress tolerance in soybean plants through complex mechanisms, including redox balance, gas exchange and changes in As accumulation pattern.